Enrich College English Teacher’s Knowledge of Summarizing Strategies Instruction and Expository Text Comprehension with Kintsch’s Reading Model - Xu, Wei (Advances in Social Sciences Research Journal, 2014)
<span style="line-height: 115%; font-family: 'Calibri','sans-serif'; font-size: 12pt; mso-fareast-font-family: 宋体; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA;" lang="EN-US">College English teachers’ knowledge of summarizing strategies instruction with expository text can be enhanced by their understanding of Kintsch’s Construction-Integration (CI) model. The argument is based on the exploration of how Kintsch’s CI model, being a reading model, could serve as a theoretical base to explain the comprehension process of expository text, and the functioning process of summarization. Rooted in cognitive theories, Kintsch’s reading model consists of two reading phases (i.e., a construction phase and an integration phase) that make it suitable to explain readers’ text comprehension process when they come across unfamiliar reading material, which is exactly the case when post-secondary students read to learn from content area textbooks mostly written in the genre of expository text. Moreover, the generation of three levels of text representation (i.e., surface structure, textbase and situation model) conveyed in this model reveal what reading strategies can be derived from this model and how one type of the reading strategies, namely, macrostructure strategies, is closely related to summarization. This relatedness is supported by researchers’ studies on and educators’ practice of summarization instruction to college students. Kintsch’s CI model is, thus, an appropriate reading model for college English teachers to add to their knowledge base to facilitate their teaching of summarizing strategies with expository text at the tertiary level.